IMPLEMENTASI PROGRAM LITERASI SAINS BERBASIS ICT DI SD NEGERI 07 KOTA BENGKULU - Endang Widi Winarni; Endina Putri Purwandari; Ferzha Putra Utama (DHARMA RAFLESIA, 2020)
The level of literacy in Indonesian is very low. Science literacy becomes very important for students to have as provisions to face the challenges of 21st-century development, including learning, innovating, critical thinking, problem-solving, creative, communication, and collaboration. Information, media, and technology literacy are becoming very important. The purpose of this activity can improve (1) teacher understanding of ICT media for literacy learning,(2) students' knowledge about animal conservation using ICT-based literacy media, and (3) student responses about ICT-based literacy media. The target audiences are (1) teacher, and (2) grade IV A and B students from State Elementary School Number 07 in Bengkulu City. The activity was carried out on the thematic learning theme 3 Caring for Living Things, Subtheme 2 Diversity of Living Things in My Environment using the ICT Based Project Based Learning model. The methods used: presentations, Focus Group Discussion, simulations and demonstrations, and classroom learning practices. The instruments used a teacher questionnaire, student responses, and essay questions. The conclusions obtained: (1) the percentage for teacher understanding of ICT literacy is still low, about 54.55%, (2) students with good categories about animal life knowledge by 93.1%, and (3) student interest on ICT learning increase about 84.62%. Suggestions given to support the successful implementation for the literacy program in elementary schools, are: (1) teachers should be able to use ICT-based learning media both on- line and off-line; (2) teachers design an assessment of students' high-level thinking knowledge.